Psychophysiological Effects of Slow-Paced Breathing on Adolescent Swimmers’ Subjective Performance, Recovery States, and Control Perception - Quentin Merlin; Philippe Vacher; Laurent Mourot; Guillaume Levillain; Guillaume Martinent; Michel Nicolas (Journal of Functional Morphology and Kinesiology, 2024)
This study examined the effect of a Slow-Paced Breath (i.e., 6 breaths per minute) without Biofeedback (SPB-NoHRVB) protocol on semi-elite adolescent swimmers’ psychological and physiological states during a seven-week ecological training period. A linear mixed-effects multilevel regression analysis approach was used with 13 adolescent national-level swimmers. Athletes were randomly assigned to an intervention group (n = 7) and a control group (n = 6). Seven waves of assessments were completed weekly during a seven-week training preparation in ecological conditions. During the protocol, swimmers completed subjective quantitative measures (RESTQ-36-R-Sport; cognitive perceived stress and control states about the training process, training subjective performance, and subjective internal training load) and physiological heart rate (HR) (HR of exercise, absolute and normalized HR recovery during the first 60 s of recovery; HRR60 and nHRR60) and heart rate variability (HRV) (MeanRR, RMSSD, LFnu and HFnu, LF/HF ration) tests (through a submaximal heart rate (5′-5′ test) once a week. Results revealed that the SPB-NoHRVB protocol significantly predicts biopsychosocial recovery states, cognitive perception of control, and training subjective performance (i.e., a significant effect of the SPB-NoHRVB protocol with the dependent variables simple time trajectories). However, no significant effects were found for biopsychosocial stress scales, cognitively perceived stress, HR, or HRV markers. Our results suggest that SPB-NoHRVB induces simple evolutions over time for crucial variables in athletes’ adaptation to the training process (i.e., cognitive appraisals and biopsychosocial states). In contrast, it highlights that SPB-NoHRVB does not induce better stress states. This specific effect on the resource component is an exciting result that will be discussed in the manuscript.